Comparative Study on the Tribological Performances of Barium Perrhenate, Molybdenum Disulfide, and Calcium Carbonate as Lubricant Additives in a Wide Temperature Range. Issue 1 (2nd January 2016) - Wang, Junhai; Liu, Yang; Duan, Deli; Li, Shu
ABSTRACT: Barium perrhenate [Ba(ReO4 )2 ], a compound used as an oil additive, was synthesized via the aqua-solution method. Its tribological properties were examined using the four-ball test and ball-on-disc tribotester in a wide temperature range and compared with those of oil that contained the additive molybdenum disulfide (MoS2 ) and calcium carbonate (CaCO3 ) compound. X-ray diffraction analysis, scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and differential thermal analysis/thermogravimetry were performed to determine the possible mechanism of the antifriction behavior of the lubricants. Results of the four-ball test showed that all of the additives can improve the extreme pressure property of the base oil and decrease the wear scar diameters of low-carbon steel balls. The results of the ball-on-disc test suggested that the MoS2 additive exhibited better lubrication property than the Ba(ReO4 )2 and CaCO3 additives at below 450°C. The CaCO3 additive displayed moderate performance in friction reducing in the high-temperature period. The Ba(ReO4 )2 additive exhibited preferable comprehensive antifriction performance in a wide temperature range because of its intrinsic shear-susceptible property and crystalline change with varied temperatures, which could form a protective layer with some native oxides of the disc sample and thus effectively prevented direct contact between rubbing parts. The detailed friction-reducing mechanism of the three additives is also discussed.